Implementasi Peraturan Bupati Karanganyar Nomor 59 Tahun 2021 Tentang Tata Cara Penegakan Disiplin Aparatur Sipil Negara di Lingkungan Pemerintah Kabupaten Karanganyar di Dinas Kesehatan Kabupaten Karanganyar - Pranata, Bagus Indra; Agustiwi, Asri (Sharia Journal and Education Center Publishing, 2024)
Abstract The purpose of this study is to determine the implementation of Karanganyar Regent Regulation Number 59 of 2021 concerning Procedures for Enforcement of State Civil Apparatus Discipline within the Karanganyar Regency Government at the Karanganyar Regency Health Office The type of research used in this thesis is sociological juridical research, which focuses on behavior that develops in society, or the operation of law in society. The data used used primary data in the form of interviews and secondary data consisting of primary, secondary and tertiary legal materials. Data collection using interviews, observation and literature study. The results showed that: Disciplinary enforcement against the State Civil Apparatus within the Karanganyar Regency government, especially the Karangnyar Regency Health Office, is in accordance with Karanganyar Regent Regulation Number 59 of 2021 concerning Procedures for Enforcement of State Civil Apparatus Discipline within the Karanganyar Regency Government. The Head of the Karanganyar Regency Health Office conducts an examination of the State Civil Apparatus suspected of committing an offense before being sentenced to disciplinary punishment. The examination is carried out in private through direct or virtual face-to-face and is outlined in the examination news. Keywords: Discipline Enforcement, State Civil Apparatus, Health Office Abstrak Tujuan penelitian ini adalah untuk mengatahui implementasi Peraturan Bupati Karanganyar Nomor 59 Tahun 2021 Tentang Tata Cara Penegakan Disiplin Aparatur Sipil Negara di lingkungan Pemerintah Kabupaten Karanganyar di Dinas Kesehatan Kabupaten Karanganyar Jenis penelitian yang digunakan dalam skripsi ini adalah penelitian yuridis sosiologis, yang berfokus pada perilaku (behavior) yang berkembang dalam masyarakat, atau bekerjanya hukum dalam masyarakat. Data yang digunakan menggunakan data primer yang berupa wawancara dan data sekunder yang terdiri dari bahan hukum primer, sekunder dan tersier. Pengumpulan data menggunakan wawancara, observasi dan studi kepustakaan. Hasil penelitian menunjukkan bahwa: Penegakan disiplin terhadap Aparatur Sipil Negara dilingkungan pemerintahan Kabupaten Karanganyar, khususnya Dinas Kesehatan Kabupaten Karangnyar telah sesuai dengan Peraturan Bupati Karanganyar Nomor 59 Tahun 2021 Tentang Tata Cara Penegakan Disiplin Aparatur Sipil Negara di lingkungan Pemerintah Kabupaten Karanganyar. Kepala Dinas Kesehatan Kabupaten Karanganyar melakukan pemeriksaan kepada Aparatur Sipil Negara yang diduga melakukan pelanggaran sebelum dijatuhi hukuman disiplin. Pemeriksaan dilakukan secara tertutup melalui tatap muka langsung maupun virtual dan dituangkan dalam berita pemeriksaan. Kata Kunci: Penegakan Disiplin, Aparatur Sipil Negara, Dinas Kesehatan